Lima Bentuk Inovasi dalam Pengajaran dan Pembelajaran Subjek Tafsir Maudu’i dalam Kalangan Pelajar Fakulti Pengajian Quran dan Sunnah, USIM - Norullisza Khosim; Hayati Hussin; Abdulloh Salaeh (Penerbit USIM, 2024)
Through diversity in technology nowadays, innovation in teaching and learning has been adapted to the subject of Thematic Exegesis among students in higher learning institutions including new pedagogy approaches such as language use, teaching style changes, technological developments and so on. This article will study the thematic approach by highlighting the particular theme handled by the Qur'an in teaching and learning Thematic Exegesis subject in the Faculty of Quran and Sunnah Studies (FPQS). Secondly, this study will explore the innovations that have been introduced and applied throughout the teaching and learning process of the subject among students of Quran and Sunnah Studies (QS) and Quran with Multimedia (QM) at the FPQS, USIM. This article uses qualitative methods through observation and documentation. The study found that: (a) there are five types of innovation in the teaching and learning of thematic exegesis subject among students; acting, wayang kulit (shadow puppets) or animation, multimedia presentations, music and lyric, and, choral speaking, (b) students have shown an improvement in innovative approaches in learning the subject of thematic exegesis especially in communication and technology.